2013
DOI: 10.1063/1.4773575
|View full text |Cite
|
Sign up to set email alerts
|

Ejecta source model based on the nonlinear Richtmyer-Meshkov instability

Abstract: Articles you may be interested inReshocked Richtmyer-Meshkov instability: Numerical study and modeling of random multi-mode experiments Phys. Fluids 26, 084107 (2014); 10.1063/1.4893678 Simulations and model of the nonlinear Richtmyer-Meshkov instability Phys. Fluids 22, 014104 (2010); 10.1063/1.3276269 Richtmyer-Meshkov instability induced by shock-bubble interaction: Numerical and analytical studies with experimental validationWe describe a simple algebraic model for the particulate spray that is ejected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(62 citation statements)
references
References 43 publications
3
58
0
1
Order By: Relevance
“…Indeed, it can not only perturb the diagnostics (electrical and optical) implemented to characterize the dynamics of the material (for instance the measurement of its free surface velocity) but it can also be a source of inhibition in applications like inertial confinement fusion [1]. The ultimate goal is to implement an ejecta source model that is able to predict both the total amount of ejected mass and the distribution of this mass, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it can not only perturb the diagnostics (electrical and optical) implemented to characterize the dynamics of the material (for instance the measurement of its free surface velocity) but it can also be a source of inhibition in applications like inertial confinement fusion [1]. The ultimate goal is to implement an ejecta source model that is able to predict both the total amount of ejected mass and the distribution of this mass, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in the example shown in Fig. 3, surface densities σ jet max at 78 ns, as defined in [6], drop from 3.02 mg/cm² (without random noise) to 1.95 mg/cm² (with random noise). However, the amplitude of the random noise is fully arbitrary at this preliminary stage.…”
Section: Radioss (Altair) (A)mentioning
confidence: 99%
“…The first one is based on a hydrodynamic analysis of two-dimensional (2D) wave propagation [3], introducing new variables like the deviation angle φ behind the front (either shock or release), coupled with a geometrical, steadystate description of wedge-shaped charges [4] assuming incompressible fluid behavior. The second approach is the Richtmeyer-Meshkov instability (RMI) theory, which was originally developed to address the spikes forming at the shock-loaded interface between two fluids of different densities, then was successfully used to treat jetting from periodical defects [5,6]. Here, this theory is applied to a single sinusoidal groove (approaching the triangular shape), assuming non-linear growth in a compressible solid with or without accounting for its elasto-plastic behavior.…”
Section: Experiments and Theorymentioning
confidence: 99%
“…Further, simulations of ejecta formation from the nanometer to centimeter scales was also reported [42,47]. The effects of shapes of the surface perturbations on the surface perturbations was first reported in [6], but the 2010s also saw the shape of the perturbations on the ejecta source studied with molecular dynamics (MD) simulations [47,48].…”
Section: Smentioning
confidence: 99%
“…The present decade has seen the application of proton radiography to study RM unstable phenomena, and ejecta studies began to focus more on RMI physics and RMI ejecta models; research on RMI models is now extensively reported [39][40][41][42].…”
Section: Smentioning
confidence: 99%